Single-cell RNA sequencing reveals distinct immunology profiles in human keloid - Feng, Cheng; Shan, Mengjie; Xia, Yijun; Zheng, Zhi; He, Kai; Wei, Yingxin; Song, Kexin; Meng, Tian; Liu, Hao; Hao, Yan; Liang, Zhengyun; Wang, Youbin; et al. (Frontiers in Immunology, 2022)
Keloids, characterized by skin fibrosis and excessive accumulation of extracellular matrix, remain a therapeutic challenge. In this study, we systematically capture the cellular composition of keloids by single cell RNA sequencing technique. Our results indicated that there are significant differences in most cell types present between 12 pairs of keloid and adjacent normal tissue. We found that fibroblasts, endothelial cell, mast cells, mural cells and Schwann cells increased significantly in keloid. The proportion of mesenchymal fibroblast subpopulations in keloids was markedly higher than those in the surrounding normal skin tissue. Furthermore, we found the immune profiles between two groups varied significantly. The proportion of macrophages in the keloid was significantly elevated compared to the surrounding normal tissue, while cDC2 cells significantly decreased. Hotspot and pseudotime trajectory analysis indicated two modules of macrophage cells (Module2: highly express RNASE1, C1QA, CD163, CD14, C1QC, FCGRT, MS4A7; Module10: highly express APOC1, CTSB, CTSL, TYROBP), which exhibited characteristics of tumor-associated macrophages (TAM), were upregulated in more advanced Keloids cells. Subsequently, analysis of cellular communication networks suggested that a macrophage-centered communication regulatory network may exist in keloids and that fibroblasts in keloids may facilitate the transition and proliferation of M2 macrophages, which contributes to further comprehension of the immunological features of keloids. Overall, we delineate the immunology landscape of keloids and present new insights into mechanisms involved in its formation in this study.